Single-Cell RNA-Seq Reveals the Cellular Diversity and Developmental Characteristics of the Retinas of an Infant and a Young Child - Hu, Fangyuan; Ma, Yuting; Xu, Zaoxu; Zhang, Shenghai; Li, Jiankang; Sun, Xinghuai; Wu, Jihong (Frontiers in Cell and Developmental Biology, 2022)
The human retina, located in the innermost layer of the eye, plays a decisive role in visual perception. Dissecting the heterogeneity of retinal cells is essential for understanding the mechanism of visual development. Here, we performed single-cell RNA-seq to analyze 194967 cells from the donors of infants and young children, resulting in 17 distinct clusters representing major cell types in the retina: rod photoreceptors (PRs), cone PRs, bipolar cells (BCs), horizontal cells (HCs), amacrine cells (ACs), retinal ganglion cells (RGCs), Müller glial cells (MGs), microglia, and astrocytes (ASTs). Through reclustering, we identified known subtypes of cone PRs as well as additional unreported subpopulations and corresponding markers in BCs. Additionally, we linked inherited retinal diseases (IRDs) to certain cell subtypes or subpopulations through enrichment analysis. We next constructed extensive intercellular communication networks and identified ligand-receptor interactions that play crucial roles in regulating neural cell development and immune homeostasis in the retina. Intriguingly, we found that the status and functions of PRs changed drastically between the young children and adult retina. Overall, our study offers the first retinal cell atlas in infants and young children dissecting the heterogeneity of the retina and identifying the key molecules in the developmental process, which provides an important resource that will pave the way for research on retinal development mechanisms and advancements in regenerative medicine concerning retinal biology.